The enigma of social harm: the problem of liberalism - Raymen, Thomas (Routledge, 2023)
A Disquieting Suggestion for Criminology and Zemiology -- Social Harm in an Era of Liberal Cynicism and its Consequences -- Social Harm and its Relationship to Human Subjectivity -- The Decline of the Telos -- Morality and Desire -- Disavowed Liberalism -- Where Do We Go From Here?